2019
DOI: 10.1111/ocr.12358
|View full text |Cite
|
Sign up to set email alerts
|

Vertical growth in mono‐and dizygotic twins: A longitudinal cephalometric cohort study

Abstract: Objective The aims of this longitudinal analysis of untreated monozygotic and dizygotic twins were to investigate vertical changes of the craniofacial structures during growth, to determine the concordance between genetically twins and to assess the genetic component for the various aspects of vertical growth. Settings and sample population The sample consisted of 34 pairs of untreated monozygotic twins (23 male, 11 female) and 30 untreated dizygotic siblings of multiple birth (8 male, 8 female and 14 mixed) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The analysis of the repeated measurements showed high reliability and small limits of agreement in all instances, which supported the robustness of the method. 17 In the main analysis, at 15 years of age, 125 participants were studied, including 64 MZ twins (n ¼ 20; 31% female) and 61 DZ twins (n ¼ 29; 48% female; Table 1). Small differences were found between MZ-DZ twins for all variables, and only the lower anterior face height/face height (LAFH/FH) showed a statistically significant difference of 1.4% (as the 95% CI excluded zero).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis of the repeated measurements showed high reliability and small limits of agreement in all instances, which supported the robustness of the method. 17 In the main analysis, at 15 years of age, 125 participants were studied, including 64 MZ twins (n ¼ 20; 31% female) and 61 DZ twins (n ¼ 29; 48% female; Table 1). Small differences were found between MZ-DZ twins for all variables, and only the lower anterior face height/face height (LAFH/FH) showed a statistically significant difference of 1.4% (as the 95% CI excluded zero).…”
Section: Resultsmentioning
confidence: 99%
“…Other than LAFH/FH, all variables showed high between-twins concordance, which agreed with previous data. 17 This is understandable because twins brought up together experience a similar environment and have an identical or similar genome. 21 Nevertheless, classical heritability estimates revealed that not all variables presented similar heritability, while maxillary inclination showed the least heritability (0.22 at 15 years and 0.28 at 18 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SNPs are characterized by the wild allele substitution, which may change the amino acid sequence of a protein or directly affect the quantity, quality, and stability of gene expression [ 11 ]. Although twin studies clearly indicate that the vertical growth pattern is strongly influenced by genetic factors [ 12 ], studies investigating the aetiology of skeletal facial growth patterns have been mainly focused on variations in anteroposterior dimensions of the face [ 8 , 9 ]. The role of SNPs, however, in the development of vertical facial proportions is still poorly understood [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%